(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the problem of innovation in the refraction of the synergetic method and analyzes the concepts of synergy (synergism) and emergence. Innovations are complex, self-organizing systems that include elements, systems, and networks. A wide range of points of view is presented in the scientific literature: from complete identification to denial of synonymy of the concepts of synergy and emergence, but even in this case, some similarities are cited, as well as a comparative analysis of the concepts of emergence and additivity. Emergence is characterized by the appearance of certain properties, qualities in a common one that were not characteristic of its individual parts.